Hospital Pseudomonas aeruginosa: Surveillance of Resistance to Gentamicin and Transfer of Aminoglycoside R Factor - Maliwan, Nitaya (1975)
Tube dilution susceptibility tests in Trypticase soy broth showed that resistance to gentamicin (minimum bactericidal concentration ≧12.5 μg/ml) among hospital isolates of Pseudomonas aeruginosa increased from 13.9% in 1969 to 38.9% in 1972. Transfer of drug resistance to six aminoglycosides from one wild Pseudomonas strain to another was accomplished in recombination experiments. A carbenicillin-resistant, beta-lactamase-producing strain served as the recipient. The exconjugant was resistant not only to aminoglycosides, including amikacin, but also to all clinically employed antimicrobials. Aminoglycoside resistance in the exconjugant was cured by sodium dodecyl sulfate. This transferable aminoglycoside resistance was not mediated by adenylylation or, as judged by bioassay, by other antibiotic-inactivating or -modifying processes.